Heterosis for resistance to insect herbivores in a 3-line hybrid rice system - Horgan, Finbarr G.; Bernal, Carmencita C.; Ramal, Angelee F.; Almazan, Maria Liberty P.; Mundaca, Enrique A.; Crisol-Martínez, Eduardo (MDPI, 2024)
Three-line hybrid rice is produced by crossing male sterile (A line) rice with a fertility-restorer (R line). Fertile lines (B lines) are also required to maintain A line seed for breeding programs. We used a range of hybrids and their parental lines to assess the frequency and nature of heterosis for resistance to the whitebacked planthopper (Sogatella furcifera), brown planthopper (Nilaparvata lugens) and yellow stemborer (Scirpophaga incertulas). Heterosis is defined as trait improvement above the average of the parental lines as a result of outbreeding. Based on the results from a greenhouse study that challenged hybrids and their parental lines with each herbivore species, we found that susceptibility to planthoppers was associated with one of the eight A lines tested, but resistance was improved by crossing with a relatively resistant restorer. Higher frequencies of heterosis for susceptibility in comparisons between hybrids and their B lines suggest that susceptibility was not related to the cytoplasmic genomes of the associated sterile A lines. Furthermore, because none of the parental lines possessed currently effective resistance genes, improved resistance against planthoppers was probably due to quantitative resistance. In a related field trial, hybrids had generally higher yields than their fertile parents and often produced larger grain; however, they were often more susceptible to stemborers, leaffolders (Cnaphalocrocis medinalis) and other caterpillars (Rivula atimeta). This was largely a consequence of hybrid heterosis for plant biomass and was strongly affected by crop duration. We make a series of recommendations to improve hybrid breeding to reduce the risks of herbivore damage.